Improving batch production using line balancing and simulation in a manufacturing company - Che Rukmalhakimi Che Rahim, 1985-; Masine Md. Tap, supervisor; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2009